2013
DOI: 10.1007/s10067-013-2338-8
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate treatment for hip osteoarthritis: prospective randomized 2-year trial

Abstract: We examined the clinical efficacy of alendronate treatment for hip osteoarthritis using multiple outcome measures. Fifty patients with symptomatic hip osteoarthritis were enrolled in this prospective trial. The patients were randomly assigned to an alendronate group (35 mg/week alendronate and 600 mg/day calcium lactate) or a control group (600 mg/day calcium lactate) for 2 years. The groups were compared with regard to the following five parameters. The primary outcome measures are the following: (1) the West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 32 publications
1
26
0
2
Order By: Relevance
“…Our observations corroborate prior studies showing a decrease in urinary levels of C-terminal telopeptide of type II collagen (CTX-II) and N-terminal telopeptide of type I collagen (NTX-I) with higher dosage of risedronate over time [34,35]. A clinical study by Nishii et al using ALN to treat hip OA in humans also showed a decrease in urinary NTX-I and CTX-II [36]. It is unclear why we did not observe a significant increase in P1NP, even at later time points when there is a strong anabolic response and osteophyte formation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our observations corroborate prior studies showing a decrease in urinary levels of C-terminal telopeptide of type II collagen (CTX-II) and N-terminal telopeptide of type I collagen (NTX-I) with higher dosage of risedronate over time [34,35]. A clinical study by Nishii et al using ALN to treat hip OA in humans also showed a decrease in urinary NTX-I and CTX-II [36]. It is unclear why we did not observe a significant increase in P1NP, even at later time points when there is a strong anabolic response and osteophyte formation.…”
Section: Discussionsupporting
confidence: 90%
“…However, a 2-year randomized controlled trial of risedronate treatment revealed contradictory results, with no significant improvement of WOMAC score or joint space retention in the knee [38]. Similarly, Nishii et al observed no inhibition of OA progression in patients with treated hip OA after 2 years of ALN treatment [36]. Therefore, in spite of the growing body of clinical work investigating the subject, no definitive conclusion can be reached on the practicality of using bisphosphonates to treat patients with OA.…”
Section: Discussionmentioning
confidence: 99%
“…Though the outcome in human subjects was not as encouraging as in animal OA models 135139 , specific drugs within the bisphosphonate class did show benefit effects in a few human studies. In the most recent prospective 2-year trial, alendronate treatment successfully improved WOMAC pain score, decrease in biochemical markers in hip osteoarthritis patients 140 . Elderly women being treated with alendronate had a significantly decreased prevalence of knee OA-related subchondral bone lesion and associated with a reduction in knee pain 141 .…”
Section: Modulation Of Tgfβ Activity In Subchondral Bone As a Potentimentioning
confidence: 99%
“…Likewise trabecular microfractures, which are present in the subchondral bone of early OA articular surfaces [1], are suggested to have a role in OA initiation through localized remodeling and vascular invasion [2]. Moreover, therapeutic studies [3, 4] and investigations into both hydraulic conductance [5] and subchondral-cartilage transport [6] suggest that changes in the subchondral bone plate (SBP) as well as trabecular network are essential to understanding the pathogenesis of OA. Given the complexity and difficulty of measuring early-stage OA cartilage and bone changes in patients or live animals, an appropriate ex vivo cartilage-bone model would be beneficial for further studying the relationships between the properties of both tissues in early disease.…”
Section: Introductionmentioning
confidence: 99%